MATHEMATICAL MODEL OF ATTITUDE AND HEADING REFERENCE SYSTEM WITH BIAXIAL HORIZONTAL PLATFORM - Sushchenko, Olha (Proceedings of National Aviation University (archive), 2017)
Purpose: Operation of attitude and heading reference systems in conditions of autonomy and high accuracy requires usage of gimballed platforms. The goal of the paper is detailed research of such systems kinematics and control moments. As result the full mathematical model of the precision attitude and heading reference system with the biaxial horizontal platform was derived. Methods: Obtaining of the mathematical model is based on the theory of gyros in general and corrected gyro compasses and theory of dynamically tuned gyros in particular. The basic laws of theoretical mechanics including concepts of Euler angles and directional cosines were taken into consideration. Results: The full mathematical model of the attitude and heading reference system is developed. The mathematical models of the vertical gyro and directional gyro as components of the researched system are given. The simulation results based on the developed models are presented. Conclusions: The mathematical model of the gimballed attitude and heading reference system including the vertical gyro and directional gyro is derived. The detailed expressions for control (correction) moments are obtained. The full analysis of the researched system kinematics was carried out. The obtained results can also be useful for design of inertial navigation systems of the wide class.